(untitled) - Extavour, Winston Conrad (Geneve, 1979)
This study of the evolution of the concept of the exclusive economic zone is, in reality, a reconstruction of the dynamic processes which have characterised the international law of the sea almost from its inception.
Keywords: Economic zones (Law of the sea),Đặc khu kinh tế (Luật biển)